Cavernomas of the central nervous system: clinical and neuroimaging manifestations in 47 patients. Issue 7 (July 1991) - Requena, I; Arias, M; López-Ibor, L; Pereiro, I; Barba, A; Alonso, A; Montón, E
Abstract : Forty seven cases of central nervous system cavernous angioma (21 males and 26 females) are described. The main clinical signs were epilepsy and brainstem syndromes. Digital subtraction intra-arterial angiography, when used, failed to reveal cavernoma. CT detected many of the lesions, but the most successful supplementary diagnostic procedure was MRI which produces highly characteristic images of cavernous angioma. The diagnosis of cavernous angioma was confirmed in the 18 cases in which the tumour was removed surgically.